Brain Gymnastics-Based Group Therapy On Reducing Depression In Elderly - Mursyida, Nurul Isnaini; Surachmi, Fajar; Suheri, Titin (Jendela Nursing Journal (JNJ), 2025)
Background: depression is a prevalent psychological condition among the elderly, often arising from physiological decline and psychosocial stressors associated with aging. The risk is notably higher among older adults residing in social care institutions due to limited social engagement and reduced cognitive stimulation. Non-pharmacological interventions, such as brain gymnastics simple coordinated movements designed to enhance cognitive activity have shown potential benefits but remain underexplored in institutionalized settings. Purpose: this study aimed to evaluate the effectiveness of group activity therapy (GAT) using brain gymnastics in reducing depression levels among institutionalized elderly individuals. Methods: a pre-experimental one-group pretest–posttest design was employed. A total of 37 elderly participants experiencing mild to moderate depression were recruited through total sampling. The intervention consisted of brain gymnastics performed three times per week for two weeks, with each session lasting 15–20 minutes. Depression levels were assessed using the short-form Geriatric Depression Scale (GDS). Data were analyzed using the Wilcoxon signed-rank test. Results: the findings demonstrated a statistically significant reduction in depression scores following the intervention (p < 0.05), indicating that brain gymnastics had a meaningful positive effect on participants’ psychological well-being. Conclusion: brain gymnastics implemented within group activity therapy is an effective, low-cost, and enjoyable non-pharmacological approach to reducing depression among the elderly. The intervention supports improved cognitive stimulation, emotional engagement, and social interaction in institutional care environments.